Estimasi Risiko Kredit Obligasi Dengan Suku Bunga Stokastik Berdasarkan Probability Of Default - Surma, Odilia Gratiaplena; Dharmawan, Komang; Ida Harini, Luh Putu (Jurnal Matematika; Vol 13 No 2 (2023), 2024)
Bonds as a fairly safe short-term and long-term investment product certainly still have potential investment risks. One of the risks in bond products is credit risk in the form of default, where the issuer fails to pay obligations to investors. The Merton model is one method that can be applied in estimating credit risk on bonds. The interest rate applied in the Merton model is generally a constant interest rate so that in this study the constant interest rate will be replaced by the stochastic interest rate of the Cross Ingersoll Ross (CIR) model. This study aims to calculate the probability of default by applying the CIR model interest rate in the Merton model of BRI bank based on a bond value of 605 billion and a bond contract period of 7 years. The results of the calculation of the CIR model interest rate of 7.28% by substituting it into the Merton model calculation obtained a probability of default value of 0.0% which indicates that there is no risk of default by BRI bank at maturity